Scientific knowledge as a means and a prerequisite for discovering the essential powers of the individual - Itkulova, Leisian; Lukyanov, Arkadiy; Bikmetov, Evgeniy; Pushkareva, Marina; Valiullina, Zaynab (Linguistics and Culture Review, 2021)
Using historical-philosophical and historical-cultural material, the authors substantiate the idea that the heuristic potential of knowledge is enhanced by an in-depth analysis of its philosophical foundations. In the process of analysing knowledge in various philosophical traditions, the authors reach an activistic conception of knowledge, which includes freedom as a prerequisite for external and internal human activity. Knowledge doesn’t coincide with the absolute measurement of freedom and at the same time with the factuality of phenomenal being. It realizes itself at the point of unity of these considerations. By analyzing the sensual, empirical, and theoretical measurement of knowledge, the authors conclude that knowledge, as well as its structure, should be considered in a broad methodological and philosophical way, including the dialectic of knowledge and ignorance. Knowledge is related to the system of human activity. This system includes the object, subject, purpose and objectives of study. But the activity system also relates to nature of the operations performed. This nature is connected with the soul of a person, their inner world. The latter has to do with personal knowledge, latent knowledge. The purpose of the study is to analyze scientific knowledge as a prerequisite for discovering the essential powers of the individual.